Advanced content delivery, streaming, and cloud services - Pathan, Mukaddim; Sitaraman, Ramesh Kumar, 1964-; Robinson, Dom. (Hoboken, New Jersey : John Wiley & Sons, Inc., 2014)
"As the subject area of CDN gains research interest and momentum, it is crucial to stay up-to-date with recent developments of its evolutionary track, as well as the current landscape and roadmap. This book provides performance models, case studies, business analyses, and several other important components, so practicing engineers and academics can use the text as a timely reference. Provides an in-depth look at Cloud-based CDNs Includes CDN and streaming media basics and tutorials. Aimed to instruct systems architects, practitioners, product developers, and researchers. Material is divided into introductory subjects, advanced content, and specialist areas"--
"Provides market analysis as a valuable reference point for commercial entities interested in investing in the CDN business"--
""7.4 Video Optimization Services""""7.5 Operator-Hosted Cdn""; ""7.6 Cloud-Based Video Streaming""; ""7.7 Future Research Directions""; ""Acknowledgments""; ""References""; ""Part II: CDN Performance Management and Optimization""; ""Chapter 8: CDN Analytics: A Primer""; ""8.1 Introduction""; ""8.2 Why Measure?""; ""8.3 What Do We Measure?""; ""8.4 What About Business Intelligence?""; ""8.5 Measuring Stateless Delivery""; ""8.6 Billing Analytics""; ""8.7 CDN Analytics Tools""; ""8.8 Recent Trends in CDN Analytics""; ""8.9 Conclusion""; ""References""; ""Chapter 9: CDN Modeling""
Includes index.
Includes bibliographical references at the end of each chapters and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Cloud computing; Computer networks; Cloud computing; Computer networks; COMPUTERS / Computer Literacy; COMPUTERS / Computer Science; COMPUTERS / Data Processing; COMPUTERS / Hardware / General; COMPUTERS / Information Technology; COMPUTERS / Machine Theory; COMPUTERS / Reference; Cloud computing; Electronic books; Electronic books